OHP-019 Day-1 Call in an Oncology Day Unit: What Improvements?. (12th March 2013) - Tran, L; Jardin, M; Cherifi, M; Bezie, Y; Deplanque, G
Abstract : Background: The preparation in advance of anticancer drugs can decrease the waiting time of patients in oncology day units. Purpose: To establish a system of phoning patients before their session (D-1 call) to cheque their availability. A year after its deployment, we evaluated the impact of this plan. Materials and Methods: The oncologist and a nurse call patients one day before their appointment. The prescriptions are validated when the patient's condition permits it in the light of the patient's biological assessment, done in an outside medical analysis laboratory, and an interview using a standardised questionnaire. After pharmaceutical validation, anticancer drugs are prepared in the afternoon for the next day. Indicators of routine monitoring were defined. Results: A median of 13 patients with 23 planned day-hospital appointments were called the day before their appointment. An oncologist validated the treatment of 45% of the patients on D-1 and 95% of the cancer treatments were delivered on D1 before 9:00 am. The total time the patients spent in the unit was reduced from 273 minutes to 242 minutes after our plan was adopted. The average time between the end of the medical consultation and the start of the treatment went down from 79 minutes before the D-1 call to 52 minutes. In addition, 2/3 of patients received the treatment only 30 minutes after seeing their doctor. Finally, fewer than 2% of anticipated preparations were not administered. Conclusions: The D-1 call requires significant effort, but it enables us to improve the organisation of care in the oncology day unit and the preparation of the anticancer drugs by the pharmacy's production unit. The workload is more even throughout the day and is not stressful for the staff. All of this contributes to making the system safer. We are hoping to extend the D-1 call to the oncology week unit and evaluate patient satisfaction. No conflict of interest.